Improvement of Fertility in Postpartum Anoestrus Buffaloes by using Different Hormonal Protocols during Non Breeding Season - Patil, AD; Shastpure, AK; Jadhao, PD; Korde, JP; Patil, MS; Patil, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was conducted on 40 postpartum anooestrus buffaloes randomly divided into four equal groups during non-breeding season. The buffaloes were selected based on ovarian inactivity, good body condition score and overall good health. Group I was administered Ovsynch protocol + Progesterone impregnated intravaginal device (PRID). Group II was administered PRID which was removed on 7th day and GnRH 10 µg i/m was given on day of AI. Group III was administered Ovsynch protocol and Group IV was kept as untreated control. 100, 80, 80 and 00 % animals responded in groups I, II, III and IV respectively. Fix timed AI was performed in all responded buffaloes. Calcium, phosphorous, cholesterol and protein level increased (p<0.05) in respect of pregnant animal than the non-pregnant animals, the rise was more in Group I than the other Groups.The conception rate was found to be 70.00, 50.00, 62.50 and 00.00 % in Group I, II, III and IVrespectively. The overall conception rate was observed to be significantly higher in Group I, i.e., Ovsynch + PRID followed by Group III, i.e. Ovsynch protocol alone in postpartum anooestrus buffaloes during non breeding season. It can be concluded that ovsynch with progesterone based protocol is very effective for oestrus induction and improved conception rate in postpartum anooestrus buffaloes during non breeding season.